Lithium-rich manganese-based positive electrode material with ultra-large interplanar spacing and preparation method and application thereof
By preparing lithium-rich manganese-based positive electrode material with ultra-large crystal plane spacing and dense surface layer, the problem of insufficient rate performance and cycle stability is solved, and a combination of high rate and excellent cycle performance is achieved.
Patent Information
- Application Number
- CN202510360665.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-26
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-03-26
AI Technical Summary
Lithium-rich manganese-based cathode materials have shortcomings in terms of rate performance and cycle stability, especially in new energy vehicles, where the problems of low rate performance and poor cycle hinder their large-scale application.
By preparing a lithium-rich manganese-based positive electrode material with ultra-large crystal plane spacing and dense surface layer, the lithium ion kinetics of the bulk phase structure and the stability of the surface structure are improved. The specific method includes adding a specific amount of sodium during the synthesis process to induce the formation of super-large crystal plane spacing, and inducing the formation of a dense structural layer on the surface of the material through thermal post-treatment.
The high rate performance and excellent cycle stability of the material are achieved, so that the material has both high rate and long life.
Smart Images

Figure CN119890287A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of battery positive electrode material preparation, and in particular to a lithium-rich manganese-based positive electrode material with ultra-large interplanar spacing, and a preparation method and application thereof. Background Art
[0002] Lithium-rich manganese-based cathode materials have the advantages of high specific capacity and low price, but their low initial efficiency, poor cycle performance and poor rate performance hinder their large-scale application, especially the rate difference that hinders their application in new energy vehicles, because current power batteries usually require 3C fast charging and ultra-fast charging > 4C capabilities, and lithium-rich manganese has Li 2 MnO 3 After activation, the redox activity of anionic oxygen and manganese activity are involved, which limits its poor kinetic performance and leads to low rate performance. Strategies to increase the rate usually include coating conductive and lithium ion materials, doping and nano-sizing to shorten the transmission path to improve the kinetics. Expanding the lithium interlayer spacing is one of the important directions to improve the diffusion kinetics of lithium ions, but conventional lithium layer doping with large atoms Na / K and the like has very limited effects on expanding the lithium interlayer spacing. For example, Chinese patent CN104218235B discloses a dual-doped lithium-rich solid solution positive electrode composite material and its preparation method, a lithium ion battery positive electrode sheet and a lithium ion battery, doped with one or a combination of Na and K, thereby increasing the surface conductivity of the lithium-rich solid solution positive electrode material and the cycle stability during charge and discharge. For example, Chinese patent CN107215900B discloses that W doping causes the interlayer spacing to increase, which is beneficial to the rate performance, but W still has problems such as difficulty in doping and high cost.
[0003] Therefore, it is necessary to design and synthesize a larger lithium interlayer spacing to improve the transmission dynamics of lithium ions in the lithium layer, thereby improving its rate performance and ensuring its cycle stability, and solving the problems of poor rate performance and high-rate cycling of lithium-rich material structures. Summary of the invention
[0004] In view of the above problems, the present invention not only improves the lithium ion dynamics of the bulk structure, but also improves the stability of the surface structure by preparing a lithium-rich manganese-based positive electrode material with ultra-large interplanar spacing and a dense surface layer. One of the purposes of the present invention is to provide a lithium-rich manganese-based positive electrode material with ultra-large interplanar spacing.
[0005] The second object of the present invention is to provide a method for preparing the lithium-rich manganese-based positive electrode material with ultra-large interplanar spacing.
[0006] The third object of the present invention is to provide an application of the lithium-rich manganese-based positive electrode material with ultra-large interplanar spacing.
[0007] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted: In the first aspect, the present invention provides a lithium-rich manganese-based positive electrode material with a large interplanar spacing, wherein the molecular formula of the lithium-rich manganese-based positive electrode material is xLi 2 MnO 3 ·(1-x)LiMO 2 , wherein M is one or more elements selected from the group consisting of Mn, Ni, Mg, Al, Co, Cr, Fe, Ti, Mo, Ru, V, Nb, Zr and Sn, and 0.2<x≤0.6; The bulk phase of the lithium-rich manganese-based positive electrode material has an ordered arrangement structure with a (003) crystal plane spacing of >5Å, and the surface of the lithium-rich manganese-based positive electrode material has a dense structure with a crystal plane spacing of <3Å parallel to the (003) crystal plane, forming a dense layer.
[0008] In some embodiments, the bulk phase of the lithium-rich manganese-based positive electrode material is composed of three types of (003) interplanar spacing structures of different sizes: the first interplanar spacing d1 (003) , the second interplanar spacing d2 (003) and the third interplanar spacing d3 (003) , where d1 (003) >6Å, 6Å>d2 (003) >5Å, d3 (003) <4Å; <001> The spacing between the (003) crystal planes in the direction is d3 (003) |d3 (003) , d2 (003) |d1 (003) , d3 (003) |d3 (003) , d1 (003) |d2 (003) The orderly arrangement of .
[0009] “|” means “and”.
[0010] In some embodiments, the dense layer has a thickness of 3-15 nm.
[0011] In some embodiments, the dense layer consists of a repeating arrangement of structures with interplanar spacings of 2.2 Å and 2.6 Å parallel to the (003) crystal plane.
[0012] The bulk phase of the lithium-rich manganese-based positive electrode material of the present invention has an ordered arrangement with a super-large interplanar spacing of >5Å, and the surface layer has a dense layer structure with a small interplanar spacing. The interplanar spacing of the bulk lithium layer is composed of interplanar spacings of regular sizes. The first type of interplanar spacing d (003) >6Å, the second type of interplanar spacing 6Å>d (003) >5Å, third-type interplanar spacing d (003)<3.0Å. <001> The arrangement of the interplanar spacing of the lithium layer in the direction is: "third type|third type"-"second type|first type"-"third type|third type"-"first type|second type" ordered super structure, such as "2.2Å|3.3Å"-"5.3Å|6.3Å"-"3.3Å|2.2Å"-"6.3Å|5.2Å". The surface layer is a structure with dense atomic layers and small interplanar spacing.
[0013] In a second aspect, the present invention provides a method for preparing the above-mentioned lithium-rich manganese-based positive electrode material with ultra-large interplanar spacing, comprising the following steps: A manganese-rich precursor, a lithium salt and a sodium salt are mixed and sintered to form sodium, and then washed with water and subjected to thermal post-treatment to obtain a lithium-rich manganese-based positive electrode material, wherein the mass ratio of the lithium salt to the sodium salt is 100:20-100.
[0014] The manganese-rich precursor is a hydroxide precursor Mn z M 1-z (OH) 2 , M is one or more selected from Ni, Mg, Al, Co, Cr, Fe, Ti, Mo, Ru, V, Nb, Zr and Sn, wherein z>0.5; The lithium salt is one or more selected from lithium carbonate, lithium sulfate, nitrate, lithium acetate and lithium hydroxide; The manganese-rich precursor and the lithium salt are in a stoichiometric ratio.
[0015] The sodium salt is one or more selected from sodium carbonate, sodium bicarbonate, sodium nitrate and sodium acetate.
[0016] In some embodiments, the heating rate of the sodium sintering is 2-10° C. / min, the sintering temperature is 750-950° C., and the holding time is 6-20 h.
[0017] In some embodiments, the temperature of the thermal post-treatment is 100-400° C., and the time of the thermal post-treatment is 3-15 hours.
[0018] In a third aspect, the present invention provides an application of the above-mentioned lithium-rich manganese-based positive electrode material with ultra-large interplanar spacing in the preparation of lithium-ion batteries.
[0019] Beneficial effects: The present invention provides a lithium-rich manganese-based positive electrode material with ultra-large interplanar spacing, which is prepared by sodiumization and post-heat treatment. A specific amount of sodium is added in a one-time method to induce the formation of ultra-large interplanar spacing during the synthesis process and to have a superlattice ordered structure to stabilize the ultra-large interplanar spacing. In the post-heat treatment, a dense structure layer is in-situ induced on the surface of the material. <001> The arrangement of the interplanar spacing of the lithium layer in the direction is an ordered superlattice structure, which has the function of stabilizing the ultra-large spacing. The surface layer is a structure with dense atomic layers and small interplanar spacing. This superlattice structure not only improves the lithium ion transport kinetics and bulk structure stability of the bulk structure, but also the dense surface layer improves the stability of the surface structure and the electrode-interface stability.
[0020] The positive electrode material of the present invention not only improves the initial efficiency of the material, but also improves the lithium ion transfer kinetics, rate performance and cycle stability of the material, so that the material has the characteristics of both high rate and excellent cycle performance.
[0021] The present invention has been described in detail above, but the above embodiments are only illustrative in nature and are not intended to limit the present invention. In addition, this article is not limited by any theory described in the above prior art or invention content or the following examples. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 Schematic diagram of the interplanar spacing of a conventional layered lithium-rich material and the positive electrode material of the present invention, wherein (a) is a conventional layered lithium-rich material, and (b) is a positive electrode material of the present invention; Figure 2 The morphology diagrams of Comparative Example 1 and Example 1, wherein (a) is Comparative Example 1, and (b) is Example 1; Figure 3 The physical structures of Comparative Example 1 and Example 1; Figure 4 TEM image of the crystal structure and the interplanar spacing of the lithium layer of Comparative Example 1; Figure 5 TEM image of the crystal structure of Example 1; Figure 6 is the interplanar spacing of the lithium layer in Example 1, wherein (a) is the interplanar spacing of the surface layer; (b) is the interplanar spacing of the bulk phase; Figure 7 The first charge and discharge curves of Comparative Example 1 and Example 1; Figure 8 The cycle stability of Comparative Example 1 and Example 1. DETAILED DESCRIPTION
[0023] The present invention is further described below in conjunction with examples. It should be noted that the following examples are provided for illustrative purposes only and do not constitute a limitation on the scope of protection claimed for the present invention.
[0024] Unless otherwise specified, the raw materials, reagents, methods, etc. used in the examples are conventional raw materials, reagents, methods in the art.
[0025] Electrochemical performance test: Evaluation was performed using a button battery. The test was performed on a Blue Power battery test system. The charge and discharge current was set to 1C=200mAh / g, and the voltage window was 2.0-4.8V.
[0026] Crystal structure and interplanar spacing measurement characterization and method: transmission electron microscopy was used, and Gatan Digital Micrograph software was used. Specifically, a straight line perpendicular to the (003) crystal plane was drawn using a wireframe tool, and then the frame width was set to 30-50. Interplanar spacing measurement, the width between the two peaks was measured, and the interplanar spacing was obtained.
[0027] Preparation Example Precursor Preparation In a stoichiometric ratio, Mn was first synthesized by hydroxide coprecipitation method. 0.68 Ni 0.29 Co 0.03 (OH) 2 , and then mixed and sintered with lithium carbonate. The specific steps are as follows: 2M concentration nickel sulfate, manganese sulfate and cobalt sulfate solutions are prepared according to the stoichiometric ratio, the complexing agents are ammonia water and sodium tripolyphosphate, and 2M concentration sodium hydroxide solution; the two liquids are pumped into the reactor at a suitable flow rate (flow rate) and stirred at a speed of 300-800r / min. After reacting for 24 hours, the high manganese precursor is obtained after washing, filtering and drying. The precursors of other components are prepared in the same way.
[0028] Comparative Example 1 Material sintering: weigh the precursor Mn according to the stoichiometric ratio. 0.68 Ni 0.29 Co 0.03 (OH) 2 and lithium salt Li 2 CO 3 , use a high-speed mixer to mix evenly, and sinter the material: heat it at 850℃ for 10h at a heating rate of 5℃ / min, and then cool it naturally to room temperature to obtain the lithium-rich manganese-based positive electrode material Li 1.184 (Mn 0.68 Ni 0.29 Co 0.03 ) 0.816 O 2 .
[0029] Example 1 Take 12g of manganese-rich precursor Mn 0.68 Ni 0.29 Co 0.03 (OH) 2 , 7.08g lithium carbonate and 3g sodium carbonate were mixed evenly with a mixer, heated at 850℃ for 15h at a heating rate of 3℃ / min, then naturally cooled to room temperature, and then the residual sodium was washed 3-5 times with deionized water, and thermally post-treated at 300℃ for 5h to obtain a lithium-rich manganese-based positive electrode material Li with ultra-large interplanar spacing. 1.184 (Mn 0.68 Ni 0.29 Co 0.03 ) 0.816 O 2 .
[0030] Use SEM to characterize the morphology of materials, such as Figure 2 As shown, the appearance of the lithium-rich material in Comparative Example 1 is also a spherical shape of a lamellar layer. After the sodium treatment of Example 1, the primary morphology of the material is still a lamellar structure, and the thickness of the lamellar layer of the primary particles is also thinner.
[0031] The phase structure of the sample was determined by XRD. Figure 3 As shown, the structure of the lithium-rich material in Comparative Example 1 is typical R- 3 m and C 2 / m The peak position of the (003) diffraction peak of the composite layered structure material of the phase is 18.72°. After sodium treatment, the peak position of the (003) diffraction peak of the material is reduced to 18.63°, indicating that the (003) interlayer spacing is enlarged.
[0032] HR-TEM was used to further determine the size of the interplanar spacing, such as Figure 4 As shown in the figure, the high-resolution and Fourier transform images of the traditional layered lithium-rich material show that it is a typical layered material structure with a crystal plane spacing of 4.769 Å, which is a conventional crystal plane spacing. However, after sodium treatment, the crystal plane spacing can be increased and a stable structure can be formed. Figure 5 The high resolution and Fourier transform results show that the bulk phase is a layered structure with a 3-15nm reconstruction layer on the surface. Figure 6As shown, the body phase <001> The arrangement of the interplanar spacing of lithium layers in the direction is “—(“small”-“large, extra-large”-“small”-“extra-large, large”)—” (—represents a continuous, repeatable unit) an ordered superlattice structure. Such as “0.22nm-0.33nm”-“0.53nm-0.63nm”-“0.33nm-0.22nm”-“0.63nm-0.52nm”, where “extra-large” interplanar spacing refers to lithium interlayer spacing of >6 Å, and “large” interplanar spacing refers to lithium interlayer spacing of >5Å.
[0033] The electrochemical performance of lithium-rich materials with this structure is greatly improved: The first coulombic efficiency, such as Figure 7 As shown in Tables 1 and 2, the first-week specific capacity of Comparative Example 1 increased from 232.2 mAh g -1 Increased to 272 mAh g -1 .
[0034] The rate performance is shown in Table 1. The capacities of comparative examples 10.33C, 0.5C, 1C, 3C, and 5C are 204.9, 200.1, 190.3, 168.1, and 154.2 mAh / g, respectively; while the rate performance of Example 1 with an ultra-large intercrystalline spacing after sodiumization is 258.6, 237.9, 246, 200.2, and 184.1 mAh / g, respectively, and the rate capacity has been greatly improved.
[0035] The cycle performance is shown in Table 2. The 1 C initial discharge capacity of the sample in Comparative Example 1 is 185.9 mAh g -1 After 200 cycles, it dropped to 155.1 mAh g -1 The capacity retention rate is 83.4%; while the 1 C charge-discharge capacity of Example 1 with a lithium-rich material having an ultra-large crystal surface and a dense surface structure is increased to 220.1 mAh g -1 After 200 cycles, there is still 207.1 mAh g -1 The capacity retention rate is as high as 94.1%. This shows that the lithium-rich manganese-based positive electrode material obtained by this method has higher first efficiency, more optimized rate performance, higher specific capacity and better cycle stability.
[0036] Example 2 Take 12g of manganese-rich precursor Mn 0.68 Ni 0.29 Co 0.03 (OH) 2 , 6.8 g of lithium carbonate and 1.5 g of sodium carbonate, and other operations are the same as in Example 1 to obtain a new structure lithium-rich material Li 1.13 (Mn 0.68Ni 0.29 Co 0.03 ) 0.87 O 2 .
[0037] The 1 C discharge capacity of Example 2 was increased to 215.7 mAhg -1 , 200.4mAhg after 200 cycles -1 , the capacity retention rate is as high as 92.9%.
[0038] Example 3 Take 12g of manganese-rich precursor Mn 0.63 Ni 0.37 (OH) 2 , 6.2 g of lithium carbonate and 2 g of sodium carbonate, and other operations are the same as in Example 1. 1.13 (Mn 0.63 Ni 0.37 ) 0.87 O 2 .
[0039] The 1 C discharge capacity of Example 3 was increased to 214.9 mAhg -1 , 196.2mAhg after 200 cycles -1 , the capacity retention rate is as high as 91.3%.
[0040] Example 4 Take 6g of manganese-rich precursor Mn 0.65 Ni 0.35 (OH) 2 , 3.2 g of lithium carbonate and 1 g of sodium carbonate; the post-heat treatment temperature is 350° C., the treatment is 3 h, and the other operations are the same as in Example 1 to obtain a lithium-rich material Li 1.13 (Mn 0.65 Ni 0.35 ) 0.87 O 2 .
[0041] The 1 C discharge capacity of Example 4 was increased to 210.5 mAhg -1 , 205.3mAhg after 200 cycles -1 , the capacity retention rate is as high as 97.53%.
[0042] Comparative Example 2 Take 12g of manganese-rich precursor Mn 0.68 Ni 0.29 Co 0.03 (OH) 2 , 7.08 g of lithium carbonate, and 1% (0.0708 g) of sodium carbonate. Other operations are the same as in Example 1 to obtain a lithium-rich material.
[0043] The 1 C discharge capacity of comparative example 2 was increased to 191.2 mAh g -1 After 200 cycles, the capacity is 160.8 mAh g -1 , the capacity retention rate is only 84%.
[0044] Table 1 Electrochemical performance
[0045] Table 2 Cyclic stability
[0046] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit them. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that the technical solutions described in the above embodiments may be modified, or some or all of the technical features thereof may be replaced by equivalents, without departing from the spirit and essence of the claims of the present invention; and these modifications or replacements are still within the scope defined by the claims of the present invention.
Claims
1. A lithium-rich manganese-based positive electrode material with ultra-large interplanar spacing, characterized in that: The molecular formula of the lithium-rich manganese-based positive electrode material is xLi2MnO3·(1-x)LiMO2, wherein M is one or more elements selected from the group consisting of Mn, Ni, Mg, Al, Co, Cr, Fe, Ti, Mo, Ru, V, Nb, Zr and Sn, and 0.2<x≤0.6; The bulk phase of the lithium-rich manganese-based positive electrode material has an ordered arrangement structure with a (003) crystal plane spacing of >5Å, and the surface of the lithium-rich manganese-based positive electrode material has a dense structure with a crystal plane spacing of <3Å parallel to the (003) crystal plane, forming a dense layer.
2. The lithium-rich manganese-based positive electrode material according to claim 1, characterized in that: The bulk phase of the lithium-rich manganese-based positive electrode material is composed of three types of (003) crystal plane spacing structures of different sizes: the first crystal plane spacing d1 (003) , the second interplanar spacing d2 (003) and the third interplanar spacing d3 (003) , where d1 (003) >6Å, 6Å>d2 (003) >5Å, d3 (003) <4Å; <001> The (003) crystal plane spacing in the direction is d3 (003) |d3 (003) , d2 (003) |d1 (003) , d3 (003) |d3 (003) , d1 (003) |d2 (003) The orderly arrangement of .
3. The lithium-rich manganese-based positive electrode material according to claim 1, characterized in that: The thickness of the dense layer is 3-15 nm.
4. The lithium-rich manganese-based positive electrode material according to claim 1, characterized in that: The dense layer is composed of repeated structures with interplanar spacings of 2.2 Å and 2.6 Å parallel to the (003) crystal plane.
5. A method for preparing the lithium-rich manganese-based positive electrode material according to any one of claims 1 to 4, characterized in that: The following steps are involved: The manganese-rich precursor, lithium salt and sodium salt are mixed and sintered for sodiumization, and then washed with water and subjected to thermal post-treatment to obtain a lithium-rich manganese-based positive electrode material, wherein the mass ratio of the lithium salt to the sodium salt is 100:20-100.
6. The preparation method according to claim 5, characterized in that: The manganese-rich precursor is a hydroxide precursor Mn z M 1-z (OH)2, M is one or more selected from Ni, Mg, Al, Co, Cr, Fe, Ti, Mo, Ru, V, Nb, Zr and Sn, wherein z>0.
5.
7. The preparation method according to claim 5, characterized in that: The lithium salt is one or more selected from lithium carbonate, lithium sulfate, nitrate, lithium acetate and lithium hydroxide; The sodium salt is one or more selected from sodium carbonate, sodium bicarbonate, sodium nitrate and sodium acetate.
8. The preparation method according to claim 5, characterized in that: The heating rate of sintering sodium is 2-10℃ / min, the sintering temperature is 750-950℃, and the holding time is 6-20h.
9. The preparation method according to claim 5, characterized in that: The temperature of the thermal post-treatment is 100-400°C, and the time of the thermal post-treatment is 3-15h.
10. Use of the lithium-rich manganese-based positive electrode material according to any one of claims 1 to 4 or the lithium-rich manganese-based positive electrode material prepared by the preparation method according to any one of claims 5 to 9 in preparing a lithium-ion battery.
Citation Information
Patent Citations
Lithium-rich manganese-based anode material and preparation method thereof
CN101694876A
Spherical lithium ion battery positive electrode material with nanoscale two-phase coexistence structure and synthetic method thereof
CN106252594A
Lithium-enriched manganese-based cathode material and preparation method and application thereof
CN106816601A
Ultrahigh-lithium-content material and lithium self-supplementing composite positive electrode material
CN114927777A
Positive electrode material and positive plate and battery comprising positive electrode material
CN115863604A
Cited By
Full-manganese-based lithium-rich positive electrode material with novel superlattice topological stack
CN121260789A